Dynamic shear amplification in seismic response of structural wall systems - Celep, Umut Utku. (Thesis (Ph.D.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2008., 2008)
Previous research indicates that, shear force demand in yielding walls are not proportional to the design moments calculated by code procedures and higher shear force demands develop along the wall with respect to code predictions as a consequence of the higher mode effects after the plastic hinge formation at the base of the wall. 2007 version of the Turkish Seismic Design Code takes the dynamic shear amplification phenomena into account with a constant base shear amplification factor of 1.5 regardless of the first mode period and ductility level of the wall. However, results obtained from extensive non-linear time history analyses performed on generic walls in this study indicate that dynamic shear amplifications increase with increasing first mode period, Strength Reduction Factor (R) and ground motion intensity. A dynamic base shear amplification relationship as a function of the first mode period and strength reduction factor has been proposed for the Turkish Seismic Design Code (2007), based on the regression analysis of the non-linear time history analysis. A story shear force profile has been suggested for the Turkish Seismic Design Code (2007), which is intended for not only preventing shear failures at the base but also along the height of the wall. As a side product of the nonlinear time history analyses, a moment profile has also been proposed for use in the Turkish Seismic Design Code (2007). A modal decomposition technique is presented in this study for demonstrating the effects of the higher modes on the dynamic shear amplification phenomenon.
Keywords: Earthquake engineering.; Shear walls -- Earthquake effects -- Testing.; Walls -- Earthquake effects -- Testing.